2021
DOI: 10.1002/wps.20881
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and acceptability of pharmacological, psychosocial, and brain stimulation interventions in children and adolescents with mental disorders: an umbrella review

Abstract: Top‐tier evidence on the safety/tolerability of 80 medications in children/adolescents with mental disorders has recently been reviewed in this jour­nal. To guide clinical practice, such data must be combined with evidence on efficacy and acceptability. Besides medications, psychosocial inter­ventions and brain stimulation techniques are treatment options for children/adolescents with mental disorders. For this umbrella review, we systematically searched network meta‐analyses (NMAs) and meta‐analyses (MAs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 126 publications
1
66
0
1
Order By: Relevance
“…waitlist) for controlling the therapeutic effect of nonspecific variables (33) . As a recent umbrella review has reported (36) , the effectiveness of psychotherapeutic interventions often decreases, at times becoming nonsignificant, when comparing them against control conditions with an active component.…”
Section: Strengths Of Our Meta-analysis and Systematic Reviewmentioning
confidence: 99%
“…waitlist) for controlling the therapeutic effect of nonspecific variables (33) . As a recent umbrella review has reported (36) , the effectiveness of psychotherapeutic interventions often decreases, at times becoming nonsignificant, when comparing them against control conditions with an active component.…”
Section: Strengths Of Our Meta-analysis and Systematic Reviewmentioning
confidence: 99%
“…Youth mental health has received growing attention in recent years, as evidenced by the inclusion of 104 network meta-analyses and meta-analyses of randomised controlled trials (RCTs) on mental health interventions for children and adolescents in a recent umbrella review published in 2021. 15 However, there is limited synthesised evidence on interventions and types of support available for children with hearing loss that promote psychological, emotional and behavioural well-being, prevent mental health conditions and treat conditions that do arise. In 2019, a systematic review on the assessment and treatment of behavioural disorders in children with hearing loss found limited evidence of interventions to address behavioural problems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it should be taken into consideration that apathy symptoms may not necessarily affect the performance at cognitive tests during routine visits, but still impact brain health in the long term. Alternatively, given the extensive number of investigations using brain stimulation techniques to treat mood disorders [ 55 ], the regions investigated in the present and previous studies may be selected in trials aiming at preventing clinical apathy by means of brain stimulation technologies.…”
Section: Discussionmentioning
confidence: 99%